2008
DOI: 10.1111/j.1464-410x.1971.tb12025.x
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidosis of the Urinary Bladder

Abstract: AMYLOIDOSIS is characterised by deposition, in various tissues, of a homogeneous, eosinophilic, hyaline material. Presently, most cases occur in a generalised form as a manifestation of an underlying plasma cell neoplasm (myeloma) or plasmacytic dyscrasia. On the other hand, most cases of symptomatic amyloid disease in the urinary bladder have occurred as an apparently solitary, localised tumefactive process. The lower urinary tract lesions of the disseminated form of the disease are rarely, if ever, symptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…One of these is localized nodular amyloidosis, in which nodular amyloid deposits are found in the respiratory tract, gastrointestinal tract, and urinary tract. Although the definitive diagnosis of localized amyloidosis requires confirmation of the absence of amyloid deposits in other organs, Malek et al suggest that no further search is necessary unless secondary amyloidosis is ruled out, Bence-Jones protein is negative, serum protein fraction is normal, and rectal biopsy shows no abnormalities [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these is localized nodular amyloidosis, in which nodular amyloid deposits are found in the respiratory tract, gastrointestinal tract, and urinary tract. Although the definitive diagnosis of localized amyloidosis requires confirmation of the absence of amyloid deposits in other organs, Malek et al suggest that no further search is necessary unless secondary amyloidosis is ruled out, Bence-Jones protein is negative, serum protein fraction is normal, and rectal biopsy shows no abnormalities [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The definitive diagnosis of localized amyloidosis requires confirmation of the absence of amyloid deposits in other organs. Malek et al showed no further search is considered necessary unless secondary amyloidosis is ruled out including Bence-Jones protein, serum protein fraction, and a rectal biopsy [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[122][123][124] AMYLOIDOSIS Amyloidosis may be primary to the bladder or secondarily involve the bladder as part of a systemic process. [125][126][127][128] Patients most commonly present with hematuria and irritative bladder symptoms, although a subset of patients may be detected incidentally on work-up for other processes.…”
Section: Prognosismentioning
confidence: 99%